Structure-based discovery of small molecule inhibitors of FKBP51-Hsp90 protein-protein interaction - Wang, Lisha; Kumar, Rajnish; Winblad, Bengt; Pavlov, Pavel F. (European journal of medicinal chemistry, 2024)
The heat shock protein 90 kDa (Hsp90) molecular chaperone machinery is responsible for the folding and activation of hundreds of important clients such as kinases, steroid hormone receptors, transcription factors, etc. This process is dynamically regulated in an ATP-dependent manner by Hsp90 co-chaperones including a group of tetratricopeptide (TPR) motif proteins that bind to the C-terminus of Hsp90. Among these TPR containing co-chaperones, FK506-binding protein 51 kDa (FKBP51) is reported to play an important role in stress-related pathologies, psychiatric disorders, Alzheimer's disease, and cancer, making FKBP51-Hsp90 interaction a potential therapeutic target. In this study, we report identification of potent and selective inhibitors of FKBP51-Hsp90 protein-protein interaction using a structure-based virtual screening approach. Upon in vitro evaluation, the identified hits show a considerable degree of selectivity towards FKBP51 over other TPR proteins, particularly for highly homologous FKBP52. Tyr355 of FKBP51 emerged as an important contributor to inhibitor's specificity. Additionally, we demonstrate the impact of these inhibitors on cellular energy metabolism, and neurite outgrowth, which are subjects of FKBP51 regulation. Overall, the results from this study highlight a novel pharmacological approach towards regulation of FKBP51 function and more generally, Hsp90 function via its interaction with TPR co-chaperones. [Display omitted] •Inhibitors of FKBP51-Hsp90 interaction were identified by structure-based virtual screening and multiple in vitro assays.•These inhibitors display specificity towards FKBP51 over other TPR proteins, particularly FKBP52.•Tyr355 of FKBP51 is important contributor to inhibitor's specificity.•These inhibitors can stimulate cell energy metabolism and neurite outgrowth.